Edukasi Sadari Sebagai Upaya Deteksi Kanker Payudara Di Desa Pamijen Sokaraja, Banyumas - Anggraeni, Destiny Eka; Ma’rifah, Atun Roudatul; Haniyah, Siti (Universitas Harapan Bangsa, 2025)
Breast cancer is a significant global health issue, being a leading cause of death for women in many developing countries. Early detection plays a crucial role in improving recovery rates and the life expectancy of patients. This study aims to analyze and evaluate the increase in knowledge among health cadres in Pamijen Village, Sokaraja, Banyumas, regarding Breast Self-Examination (BSE) as an effort for early detection of breast cancer. The research method involves pre-survey, health education through lectures, discussions, and demonstrations, followed by post-survey and evaluation of practices. Pre-survey results showed that the majority of cadres (47%) had a lack of knowledge regarding BSE. After the educational intervention, there was a significant increase, with 100% of the cadres demonstrating good knowledge levels. Further evaluation also showed that the cadres started to practice BSE at home and are ready to become education agents in the community.